A New Stochastic Model to Find the Insulin Secretion from Human Islets Using Exponential Distribution - Kumar, P. Senthil; Balasubramanian, K.; Kumar, A. Dinesh (IJRDO -JOURNAL OF MATHEMATICS, 2015)
Many plant based products have been suggested as potential antidiabetic agents, butfew have been shown to be effective in treating the symptoms of Type 2 diabetes mellitus(T2DM) in human studies, and little is known of their mechanisms of action. The effects of anovel high molecular weight Gymnema sylvestre (GS) extract, Om Santal Adivasi (OSA) onplasma insulin, C-peptide and glucose in a small cohort of patients with T2DM are reportedhere. Oral administrationof OSA induced significant increases in circulating insulin and Cpeptide, which were associated with significant reductions in fasting and post-prandial bloodglucose. The results of insulin secretion from human islets of langerhans were comparedusing the marginal distribution of a stretched Brownian motion